Hydrologia zlewni rzeki Kowaniec = The hydrology of the watershed of Kowaniec river - Kołodziejczyk, Urszula; Hudak, Magda; Golik, Dawid; Migda, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the characteristics of hydrographic watershed of the Kowaniec river (a tributary of the Dunajec river basin) and the water balance of the area. The analysis shows that hydrological parameters are typical for the mountain rivers and heavily forested areas. The surface supplying had a dominant character, what should be connected with intense rainfall in the period of spring and summer. The total water balance of the Kowaniec river watershed has been calculated as positive one.
Keywords: zlewnia; bilans wód; watershed; water balance